Systemic response induced by Scorpaena plumieri fish venom initiates acute lung injury in mice - Boletini-Santos, Douglas; Komegae, Evilin Naname; Figueiredo, Suely G.; Haddad, Vidal [UNESP]; Lopes-Ferreira, Monica; Lima, Carla (Pergamon-Elsevier B.V. Ltd, 2008)
Scorpaena plumieri venomous fish inflicted severe injuries in humans characterized by systemic effects and cardiovascular abnormalities. Although cardiotoxic and hypotensive effects induced in rats by this venom have been studied, little is known about their effect on bronchial epithelial permeability and airway inflammation in mice. The primary goal of this study was to determine whether the intraplantar or intraperitoneal injection of S. plumieri venom results in systemic response, and whether this event initiates acute lung injure. We found that BALB/c mice developed neutrophilic infiltrates, areas of lung hemorrhage and alveolar macrophage activation within 24 h after injection with S. plumieri venom. These histopathological changes were associated with an early increase in BAL fluid protein and early induction of cytokines, chemokines and matrix metaloproteinases, followed by a later increase in BAL fluid neutrophils. These findings provide clear evidence that the injection of S. plumieri venom in footpad or peritoneal cavity of mice results in venom deposition in the airway and initiates a sustained inflammatory response in the lungs. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Scorpaena plumieri venom; lung injury; inflammatory mediators; alveolar macrophages